2018
DOI: 10.1021/acs.joc.8b01443
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Cascade Synthesis of 2-Aryl-3-cyanobenzofuran and Dibenzo[b,f]oxepine-10-carbonitrile Derivatives

Abstract: The copper-catalyzed reaction of aryl aldehydes with 2-iodobenzylcyanides afforded 2-aryl-3-cyanobenzofurans in isolated yields of up to 74% in a cascade manner, which involves Knoevenagel condensation, aryl hydroxylation, oxa-Michael addition, and aromatization reactions. Conversely, 2-halo benzaldehydes as reacting partners with 2-iodobenzylcyanide regioselectively furnished dibenzo[ b,f]oxepine-10-carbonitrile derivatives up to 85% isolated yields via tandem Knoevenagel condensation, aryl hydroxylation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In order to obtain the target molecules conveniently, the large‐scale synthesis of the key diarylethene intermediates 2 is the most important. In fact, the first step of transformation is a similar reaction of classical Knoevenagel condensation reaction, which can be processed by several methods [26,27] . However, we desire to obtain a convenient and effective procedure for these intermediates with specific substituents, and the transformation condition was initially optimized using 3,4‐methylenedioxyphenylacetic acid 1 and 3,4,5‐trimethoxybenzaldehyde as substrates, and the different base were explored as catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain the target molecules conveniently, the large‐scale synthesis of the key diarylethene intermediates 2 is the most important. In fact, the first step of transformation is a similar reaction of classical Knoevenagel condensation reaction, which can be processed by several methods [26,27] . However, we desire to obtain a convenient and effective procedure for these intermediates with specific substituents, and the transformation condition was initially optimized using 3,4‐methylenedioxyphenylacetic acid 1 and 3,4,5‐trimethoxybenzaldehyde as substrates, and the different base were explored as catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the first step of transformation is a similar reaction of classical Knoevenagel condensation reaction, which can be processed by several methods. [26,27] However, we desire to obtain a convenient and effective procedure for these intermediates with specific substituents, and the transformation condition was initially optimized using 3,4-methylenedioxyphenylacetic acid 1 and 3,4,5-trimethoxybenzaldehyde as substrates, and the different base were explored as catalyst. The results indicated that the reaction catalyzed by DIPEA give the best isolated yields (74 %), however, the intermediate 2 b (R 1 = OCH 3 ) can also be obtained using triethylamine (42 %) and pyridine (56 %) with relatively low yields respectively.…”
Section: Synthesismentioning
confidence: 99%
“…Of late, Panda and coworkers described the synthesis of phenyldibenz[ b,f ]oxepines in two steps involving Sonagashira reaction between o ‐iododiaryl ethers and terminal alkyne to give 2‐phenoxy diaryl acetylenes in the first step, followed by FeCl 3 ‐catalyzed intramolecular C−H hydroarylation in the second step (Scheme 1a) [19a] . Later, Yao and coworkers demonstrated on the synthesis of substituted dibenzo[ b,f ]oxepine‐10‐carbonitrile via copper‐catalyzed cascade reaction of 2‐halo benzaldehydes with 2‐iodobenzylcyanide, however, the scope of the method was limited (Scheme 1b) [19b] . However, these previous reported methods for the construction of the oxepines require long reaction times, high reaction temperatures, and step‐by‐step procedure to obtain the oxepine derivatives.…”
Section: Figurementioning
confidence: 99%
“…Disubstituted aldehydes could successfully undergo the cascade reaction to afford 2‐aryl‐3‐cyanobenzofurans. The method was then extended to substituted and disubstituted 2‐iodobenzylcyanide substrates, producing corresponding 2‐aryl‐3‐cyanobenzofurans (Scheme ) …”
Section: Design and Synthesis Of Heterocycles Containing Only One Hetmentioning
confidence: 99%